judul Meningkatkan Minat Baca Siswa SMK melalui Sosialisasi Budaya Literasi : Meningkatkan Minat Baca Siswa SMK melalui Sosialisasi Budaya Literasi - Rektor Sianturi; Juli Antasari Br Sinaga; Gayus Simarmata; Peniel Sam Putra Sitorus; Jaya Tata Hardinata (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Amid the onslaught of technology and social media, vocational school students' interest in reading in Indonesia is still like a fading fire. Lack of access to books, minimal interest in reading, and an undeveloped literacy culture in the school environment are the dominant factors. This condition hampers the learning achievement and critical thinking abilities of vocational school students. The first step is to delve into the reading habits of vocational school students and the factors that influence them. The time has come for the promotion of literacy culture to be launched. Various interesting and interactive activities are packaged to attract the interest of vocational school students. Starting from counseling about the importance of reading, introduction to various types of books, to discussions and reading competitions. This is clear evidence that the socialization of literacy culture is able to revive interest in reading among vocational school students. This research concludes that literacy culture socialization is an effective way to increase vocational school students' interest in reading. Sustainable efforts are needed to instill a culture of literacy in the school environment, involving collaboration between schools, parents and the community.